Neue Erzählformen in dynamischen Bildtechnologien Formprobleme zwischen Populärkommunikation und autonomer Kunst - Grabbe, Lars C.; Rupert-Kruse, Patrick; Schmitz, Norbert M. (Bewegtbilder, 2024)
After a brief phase of playful experimentation, every advance, every major innovation in various media provokes renewed consolidation and aesthetic reflection: we have been familiar with this duality as a separation between mass communication and art since the days of industrial communication at the latest. This can also be observed in the development of the central perspective image, early photography and especially cinematography. After an initial phase of the cinema of attractions, a new and unique formal language of the Classical Style developed as a conventionalized design rule of film, which at the same time and sometimes in sharp opposition triggered various counter-movements or was reshaped as their explicit reflection by individual artistic formal languages. We are currently facing a similar situation, the invention and spread of three-dimensional dynamic techniques with data glasses and other technologies that enable new forms of virtual production and thus of storytelling - so-called 'spatial' or 'environmental storytelling'. This volume is dedicated to this new narrative on three levels: spatial image and sound (film), movement in space (computer games and VR) and space as context (AR).